FERMENTASI SUBSTRAT PADAT BUAH PISANG DAN APLIKASINYA - Anny S.; Lindajati T.; Milono p.; Roestamsjah Roestamsjah (Research Center for Chemistry - LIPI, 1991)
This study is aimed at exploring the posibility of preparing tape pisang by solid substrate fermentation method and applying the results for snack foods preparation. Two varieties of banana i.e.